Responding to the 2015 CMS Proposed Rule Changes for LTC Facilities: A Call to Redouble Efforts to Prepare Students and Practitioners for Nursing Homes. Issue 2 (17th February 2016) - Bern-Klug, Mercedes; Connolly, Robert; Downes, Deirdre; Galambos, Colleen; Kusmaul, Nancy; Kane, Rosalie; Hector, Paige; Beaulieu, Elise; ,
ABSTRACT: In July of 2015, the Federal Register published for public comment proposed rule changes for nursing homes certified to receive Medicare and/or Medicaid. If the final rules are similar to the proposed rules, they will represent the largest change in federal rules governing nursing homes since the Nursing Home Reform Act which was part of OBRA 1987. The proposed changes have the potential to enhance the quality of care and quality of life of nursing home residents. Many of the proposed changes would directly affect the practice of social work and would likely expand the role for nursing home social workers. This article discusses the role that members of the National Nursing Home Social Work Network (NNHSW Network) played in developing and submitting a response to CMS. The article provides the context for the publication of the proposed rules, describes the process used by the NNHSW Network to develop and build support for comments on these rules, and also includes the actual comments submitted to CMS. Social work education programs and continuing education programs throughout the country will continue to have an important role to play in helping to prepare social work students and practitioners for a career in long-term care.